FERTILIZERS’ EFFECT ON PRODUCTIVITY OF CAMELINA SATIVA (FALSE FLAX) - T. Ya. Prakhova; L. E. Velmiseva (Зерновое хозяйство России)
The article gives the results of effect of different doses and combinations of fertilizers on Camelina sativa (gold-of-pleasure or false flax) in the conditions of forest steppe of Middle Povolzhie.  The influence of different doses and combinations of fertilizers on productivity and quality of seed oil of Camelina sativa has been determined. The main effect of nitrogen, phosphorus and potassium on growth and development of Camelina sativa was described.  It has been determined that in all trials the use of fertilizers gave the greatest seed productivity compared with a control (without fertilizers). The fertilizers dose N30P60 increased productivity of Camelina sativa on 0,17 t/ha and oil percentage up to 40,2%. Spring Camelina sativa gave the highest productivity (1,78-1,89 t/ha) with a complex fertilizing (N20P30K20), which exceeded the indexes of the crop grown without fertilizing on 0,98-1,05 t/ha.  The conducted analysis of variance showed that the Camelina sativa productivity was greatly influenced by fertilizers (38,3%). Besides, the article gives main agro chemical traits of soil, long-term study of nutrients in Camelina sativa yield and NPK content per 1 ton in basic and side Camelina products. It has been determined that Camelina plants can endure 68,15 kg of nitrogen per 1 ton of main product and 45,72 kg of side product with seeds and 22,42 kg of it with straw. The plants can endure phosphorus least of all, 8,53 kg with seeds and 3,69 kg with straw (12,22 kg) at a whole.